THE DEVELOPMENT OF ENTREPRENEURIAL MODEL TO IMPROVE BUSINESS INDEPENDENCE SUSTAINABLE AT UNIVERSITY - Suranto Suranto; Agus Marimin; Dewi Muliasari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The aim of this research is to formulate the development of an entrepreneurial model to improve students business independence through workshop to equip entrepreneurial knowledge and internships to hone entrepreneurial skills. There were 40 students involved in this research as an experimental test, through workshop activities: business planning and analysis, business model canvas and MSME internship activities to hone skills through making business prototypes and marketing products for the students. Testing through a pretest and post-test is carried out through control group design field experiment approach. The result is goodness of fit model formulation which is able to increase students’ business independence. Keywords: competency, knowledge, skills, efforts, students